Value of Assessing Autonomic Nervous Function by Heart Rate Variability and Heart Rate Turbulence in Hypertensive Patients - Yijun Yu; Yanling Xu; Mingjing Zhang; Yuting Wang; Wusong Zou; Ye Gu (International Journal of Hypertension)
Purpose. To explore the relationship between blood pressure control and autonomic nervous function assessing by heart rate variability (HRV) and heart rate turbulence (HRT) in hypertensive patients. Methods. A total of 120 consecutive hypertensive patients and 80 nonhypertensive patients (N-HP group) were enrolled in this study. The hypertensive patients were divided into controlled blood pressure and uncontrolled blood pressure groups according to their blood pressure on admission. All subjects underwent 24-hour Holter monitoring. This study compared HRV and HRT in nonhypertensive and hypertensive patients and hypertensive patients with controlled and uncontrolled blood pressure. HRV parameters include square root of mean of the sum of squares of successive NN interval differences (rMSSD), number of successive NN intervals differing by > 50ms divided by the total number of successive NN intervals (pNN50), very low frequency (VLF) at frequency between 0.0033 and 0.04 Hz, low frequency (LF) at frequency between 0.04 and 0.15 Hz, and high frequency (HF) at frequency between 0.15 and 0.4 Hz. Turbulence slope (TS) belongs to HRT parameters. Results. TS, rMSSD, pNN50, VLF, LF, and HF values were significantly lower in the HP group than in the N-HP group. Multiple logistic regression analysis showed that reduced TS, rMSSD, pNN50, LF, and HF values were risk factors of hypertension. TS, rMSSD, pNN50, VLF, LF, and HF values were significantly lower in hypertensive patients with uncontrolled blood pressure than in hypertensive patients with controlled blood pressure. Multiple logistic regression analysis showed that reduced TS, rMSSD, pNN50, VLF, LF, and HF values were risk factors for uncontrolled blood pressure. Conclusions. This study indicates impaired autonomic nervous function in hypertensive patients, especially in hypertensive patients with uncontrolled blood pressure despite guideline recommended antihypertensive medications.